THE IMPORTANCE OF MORAL VALUES EDUCATION IN TEACHER TRAINING - Gasimova , Aynur (Collection of scientific papers «ΛΌГOΣ», 2023)
It can be said that values have a very serious impact on the functioning of the individual. A person who concentrates these values in his professional activity and is an example for society by his personality is a teacher. It is no accident that the future of every nation depends on decent citizens, and the education of these citizens depends on the teacher. The level of education and training of teachers throughout history have made both Eastern and Western educators and thinkers think, distinguished by the authority of the teacher, his culture, humanism in communicating with people, kindness, norms of moral and ethical behavior.